Guyana : public sector review (World Bank WashingtonUS, 1993)
Examines the role of the public sector. Identifies priority areas where government should focus its limited resources to address Guyana's key development issues within the framework of the Economic Recovery Programme. Assesses the need for further external assistance and debt relief to achieve external viability and sustainable growth.
DC